Nueva guia para la conduccion de pruebas regionales de yuca - Toro, Julio C.; Celis, E.; Jaramillo, Gustavo (International Center for Tropical Agriculture, 1983)
A guideline for carrying out regional trials in cassava is given, including necessary steps (identification of collaborators, selection of sites, identification of person in charge, planting and harvesting season, exptl. design, plot size, and border rows); the technology used (selection and treatment of cuttings, plant density, land preparation, planting position, application of herbicides and fertilizers, pest and disease control); necessary visits (a min. of 7); and final agronomic trials to determine optimum density and age of var. at harvest. (CIAT)